Discontinuous micro-fibers as intrinsic reinforcement for ductile Engineered Cementitious Composites (ECC). (1st March 2020) - Zhang, Duo; Yu, Jing; Wu, Haoliang; Jaworska, Beata; Ellis, Brian R.; Li, Victor C.
Abstract: Engineered Cementitious Composites (ECC) have demonstrated superior mechanical and durability performance than conventional concrete. In the micromechanical reinforcing system of ECC, fibers play a pivotal role in establishing the ultrahigh tensile ductility and autogenous crack width control. This article reviews the state-of-the-art of discontinuous micro-fibers as intrinsic reinforcement of ECC regarding technical performance as well as environmental and economic impacts. Mechanical properties of ECC made with different micro-fibers, man-made or natural, and their embodied energy, emissions and material cost, are comprehensively surveyed. Further, studies on fiber hybridization are discussed regarding the combination of different types of fibers to form synergetic reinforcements that mitigate total material cost, and potentially enhance the composite performance. Recommendations on fiber selections are highlighted and directions for future research are suggested.